Fatty acid neutral losses observed in tandem mass spectrometry with collision‐induced dissociation allows regiochemical assignment of sulfoquinovosyl‐diacylglycerols. (3rd February 2013) - Zianni, Rosalia; Bianco, Giuliana; Lelario, Filomena; Losito, Ilario; Palmisano, Francesco; Cataldi, Tommaso R.I.
Abstract : A full characterization of sulfoquinovosyldiacylglycerols (SQDGs) in the lipid extract of spinach leaves has been achieved using liquid chromatography/electrospray ionization‐linear quadrupole ion trap mass spectrometry (MS). Low‐energy collision‐induced dissociation tandem MS (MS/MS) of the deprotonated species [M − H] − was exploited for a detailed study of sulfolipid fragmentation. Losses of neutral fatty acids from the acyl side chains (i.e. [M − H − RCOOH] − ) were found to prevail over ketene losses ([M − H − R'CHCO] − ) or carboxylates of long‐chain fatty acids ([RCOO] − ), as expected for gas‐phase acidity of SQDG ions. A new concerted mechanism for RCOOH elimination, based on a charge‐remote fragmentation, is proposed. The preferential loss of a fatty acids molecule from the sn ‐1 position (i.e. [M − H − R1 COOH] − ) of the glycerol backbone, most likely due to kinetic control of the gas‐phase fragmentation process, was exploited for the regiochemical assignment of the investigated sulfolipids. As a result, 24 SQDGs were detected and identified in the lipid extract of spinach leaves, their number and variety being unprecedented in the field of plant sulfolipids. Moreover, the prevailing presence of a palmitic acyl chain (16:0) on the glycerol sn ‐2 position of spinach SQDGs suggests a prokaryotic or chloroplastic path as the main route for their biosynthesis. Copyright © 2013 John Wiley & Sons, Ltd.